1994
DOI: 10.1097/00006842-199407000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported hostility and suicidal acts, accidents, and accidental deaths: a prospective study of 21,443 adults aged 25 to 59.

Abstract: The association of self-reported hostility with morbidity and mortality due to external causes, including suicidal acts, was analyzed in 10,586 Finnish men and 10,857 Finnish women aged 24 to 59 years. Hostility was assessed from self-ratings on irritability, ease of anger-arousal, and argumentativeness. Three groups, low (33.6% of subjects), intermediate (50.6%), and extreme (15.9%), were formed from the self-reported hostility scores. A 6-year mortality follow-up yielded 76 violent deaths among men and 11 am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
1
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(75 citation statements)
references
References 0 publications
2
71
1
1
Order By: Relevance
“…Item ratings were on a 7-point, Likert-type scale. The hostility measure has been shown to be reliable and valid, and has been successfully used in prospective studies to predict absence through sickness, hospitalization, coronary heart disease and mortality (Romanov et al 1994 ;Strandberg et al 1994 ;Vahtera et al 1997). The internal consistency and long-term stability of the scale were satisfactory in our sample (coefficient alpha reliability 0n77, 3-year test-retest reliability 0n67).…”
Section: Methodsmentioning
confidence: 69%
See 1 more Smart Citation
“…Item ratings were on a 7-point, Likert-type scale. The hostility measure has been shown to be reliable and valid, and has been successfully used in prospective studies to predict absence through sickness, hospitalization, coronary heart disease and mortality (Romanov et al 1994 ;Strandberg et al 1994 ;Vahtera et al 1997). The internal consistency and long-term stability of the scale were satisfactory in our sample (coefficient alpha reliability 0n77, 3-year test-retest reliability 0n67).…”
Section: Methodsmentioning
confidence: 69%
“…It has been reported that hostility contributes to various health problems and diseases (Barefoot et al 1983(Barefoot et al , 1989Shekelle et al 1983 ;Smith & Frohm, 1985 ;Dembroski et al 1989 ;Romanov et al 1994 ;Miller et al 1996). Although findings are not wholly consistent, most research results suggest that hostile individuals are at greater risk of coronary heart disease (Ostfeld et al 1964 ;Barefoot et al 1983 ;Koskenvuo et al 1988 ;Julkunen et al 1994) and that hostility also causes minor health problems (Houston & Kelly, 1989 ;Chen & Spector, 1992 ;Siegler et al 1992 ;Kivima$ ki et al 1996 ;Vahtera et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…32,33 All analyses were adjusted for age (continuous variable). We also examined the following potential confounding factors: zygosity (monozygotic, dizygotic), 41 social class (blue collar, intermediate, white collar), 42 age at birth of first child (Ͻ25, Ն25 years), 36 number of children (0, 1-2, Ն3), 36 use of oral contraceptives (never, ever), 36 body mass index (Ͻ25, 25-29, Ն30 kg/m 2 ), 40 alcohol use (0, 1-399, Ն400 g/month), 43 smoking (never smoker, occasional smoker, ex-smoker, current smoker) 44 and physical activity in leisure time (sedentary, occasional, conditioning exerciser).…”
Section: Discussionmentioning
confidence: 99%
“…The scale has been validated by demonstrating a significant correlation (r ϭ 0.62) with the Spielberger's Trait-Anger scale. 33 The scale has also been shown to have predictive validity. [32][33][34] As for reliability, the internal consistency (␣ ϭ 0.79) and 9-year test-retest reliability (r ϭ 0.57) 33 are good.…”
Section: Assessment Of Extroversion Type a Behaviour And Hostilitymentioning
confidence: 99%
See 1 more Smart Citation